Serum Magnesium and Vitamin D Levels as Indicators of Asthma Severity - Shaikh, Mohammed Nadeem; Malapati, Brahma Reddy; Gokani, Ruchi; Patel, Bhavita; Chatriwala, Mitul (Pulmonary Medicine, 2016)
Background. Serum magnesium levels affect the concentration of circulating vitamin D in blood and subsequently it affects the immunity; thus it plays significant role in the pathogenesis of asthma. Asthma, in adults, is less studied and hypomagnesemia along with vitamin D deficiency and insufficiency is common in asthmatic individuals, which causes frequent asthma attacks, respiratory infections, severe exacerbations, and poor response to bronchodilators. Objective. To detect the magnitude of vitamin D insufficiency and deficiency and serum magnesium levels among asthmatic patients and to correlate them with the severity of asthma. Materials and Methods. This is a cross-sectional case-control study which includes 60 patients of chronic stable asthma and 60 healthy controls. After taking clinical history and systemic examination, pulmonary function test was done. Serum levels of magnesium, 25-hydroxycholecalciferol [25(OH)D], and calcium were measured in all the subjects. Results. Significant correlation was found between vitamin D deficiency, hypomagnesemia, and asthma severity. Serum calcium levels were unaffected by that. Conclusion. Vitamin D and serum magnesium deficiency are highly prevalent in patients with asthma. Increased asthma severity, frequency of attacks, and exacerbation are associated with lower levels of one or both. Serum 25(OH)D and magnesium levels may serve as important markers of asthma severity.